Uma proposta lúdica com utilização do GeoGebra para o estudo de funções quadráticas e probabilidade geométrica - Canavezi, Leandro Souza (Universidade Federal de São Carlos, 2016)
This paper reports the idealization, planning, construction and implementation of activities for the study of quadratic functions and geometric probability for classes of 9th grade of elementary school. It also presents the analysis of the activities undertaken by pupils and conclusions about the proposed objectives and goals achieved. The main objective of the developed activities is to provide students a better learning content covered and issues through a playful approach, interactive and motivating. The specific objectives are to develop the ability to translate a mathematical problem in mathematical language, manipulate algebraic expressions, estimates and comparisons, develop mathematical knowledge as knowing how to express and calculate the area and perimeter of plane figures, calculating probabilities of random events, solve quadratic equations, plotting graphs of quadratic functions and manipulate the software or the GeoGebra application. For this we have created a game of darts adapted and activity sheets containing instructions, questions, tables, graphs, calculation exercises, optimization problems and graphic constructions scripts applied to GeoGebra. The methodology used was the Didactic Engineering. The activities were implemented in two classes of 9th grade of elementary school in two different schools, one class at a school in the municipal school of Bauru, São Paulo, and another class of a school in the state school system the city of Agudos, state of São Paulo. During the application were used 12 50-minute lessons in two classes, with six days of double classes, in which students actively participated in all activities. Our work makes reference to the National Curriculum Parameters (PCN) and other documents governing the teaching of mathematics in public schools in Brazil. We recommend and authorize reproduction of these activities for didactic purposes.
Keywords: Funções quadráticas; Probabilidade geométrica; Problemas de otimização; GeoGebra; Engenharia didática; Quadratic functions; Geometric probability; Optimization problems; GeoGebra; Didactic engineering; CIENCIAS EXATAS E DA TERRA::MATEMATICA